Knowledge Attitude and Practices towards prevention of Diabetes Mellitus among Patients aged 25-70 years in Wakiso Health Centre IV, Wakiso District. A Cross-sectional Study. - Bridget Charity Malunga (Student's Journal of Health Research Africa, 2022)
Background: